2016
DOI: 10.1111/jcmm.12858
|View full text |Cite
|
Sign up to set email alerts
|

miR‐19b controls cardiac fibroblast proliferation and migration

Abstract: Cardiac fibrosis is a fundamental constituent of a variety of cardiac dysfunction, making it a leading cause of death worldwide. However, no effective treatment for cardiac fibrosis is available. Therefore, novel therapeutics for cardiac fibrosis are highly needed. Recently, miR‐19b has been found to be able to protect hydrogen peroxide (H2O2)‐induced apoptosis and improve cell survival in H9C2 cardiomyocytes, while down‐regulation of miR‐19b had opposite effects, indicating that increasing miR‐19b may be a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…According to previous report, up-regulation of miR-19b inhibits apoptosis and activates the AKT pathway by down-regulating PTEN. 52 Here, we performed bioinformatics analysis using the RegRNA 2.0 database (http://regrna.mbc.nctu.edu.tw/html/predi ction.html) to identify the miRNAs that contain potential binding sequences for CHAR. The database predicts no potential binding site or sequence complementarity between CHAR and miR-19b.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous report, up-regulation of miR-19b inhibits apoptosis and activates the AKT pathway by down-regulating PTEN. 52 Here, we performed bioinformatics analysis using the RegRNA 2.0 database (http://regrna.mbc.nctu.edu.tw/html/predi ction.html) to identify the miRNAs that contain potential binding sequences for CHAR. The database predicts no potential binding site or sequence complementarity between CHAR and miR-19b.…”
Section: Discussionmentioning
confidence: 99%
“…Over-expression of miR-19b decreased the infarct area and restored the left ventricular systolic function and volume load of mice with HF after myocardial infarction (MI) by inhibiting cardiac apoptosis. 10,11 According to a recent review, an important factor driving progression from myocardial hypertrophy to HFpEF was the proliferation of an abnormal fibroblast phenotype, which may degrade normal stromal matrix and was replaced by a fibrotic matrix structure. 12 Ravassa et al 13 reported that HFpEF was characterized by increased collagen cross-linking and involved in left ventricular diastolic dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Mir‐148 was a repressor of NF‐kB signalling, playing roles in cardiac injury 32. In addition, miR‐19 was demonstrated to involve in cardiac remodelling by controlling cardiac fibroblast proliferation and migration 33. Moreover, in “loss” module, a number of heart failure‐related miRNAs were also extracted.…”
Section: Resultsmentioning
confidence: 99%
“…32 In addition, miR-19 was demonstrated to involve in cardiac remodelling by controlling cardiac fibroblast proliferation and migration. 33 Inhibition of miR-15 family could reduce infarct size and cardiac remodelling and enhance cardiac function in response to MI. 35 Huang et al demonstrated that overexpression of miR-16 could provoke cardiomyocyte hypertrophy by derepressing the cyclins D1, D2 and E1, and activating cyclin/Rb pathway.…”
Section: Identification Of Dysregulated Cerna Interactions In Networkmentioning
confidence: 99%